Cell‐Penetrating Peptides and Polymers for Improved Drug Delivery. Issue 8 (20th April 2020) - Gui, Lin; Zhang, Xue‐Hao; Qiao, Zeng‐Ying; Wang, Hao
Abstract: Effective delivery of biologically active compounds including peptides, proteins, and nucleic acids into cells is an obstacle in the drug research. The intracellular delivery of biological agents generally relies on the endocytosis pathway, causing them to be trapped in endosomes and lysosomes. Cell‐penetrating peptides (CPPs) have previously been shown to be a useful transport tool for delivering many kinds of goods into cells through cell membranes. The latest discovery of cell penetrating poly(disulfide)s (CPDs) with excellent cytosolic delivery efficiency represents a major breakthrough in this field. In this work, we will focus on the latest advances in biological applications of the CPPs and new opportunities opened up by the CPDs. Abstract : Cell penetrating peptides (CPPs) have been demonstrated to be powerful transporters for the intracellular delivery of many cargos. Their intracellular delivery usually depends on the endocytic pathway resulting in endosome and lysosome trapping. The recent discovery of cell‐penetrating poly(disulfide)s (CPDs) with extraordinary high cytosolic delivery efficiencies represents endosome‐independent feature due to the dynamic covalent disulfide bond.